2013
DOI: 10.4238/2013.october.30.2
|View full text |Cite
|
Sign up to set email alerts
|

Association of paraoxonase polymorphisms with carotid artery atherosclerosis in essential hypertension patients

Abstract: ABSTRACT. We investigated the relationships between paraoxonase genetic polymorphisms and essential hypertension in carotid artery atherosclerotic patients. The study included 353 Han participants and 240 Uighur participants from Xinjiang; they were further divided into two groups: essential hypertension with carotid artery atherosclerosis (CAAD group) and essential hypertension without carotid artery atherosclerosis (control group). Genotypes were detected by PCR, followed by restriction analyses with specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…21 PON1 was also significantly differentially expressed between HF and non-HF patients and significantly associated with HFrEF. Studies in two Japanese patient cohorts have revealed that the presence of certain alleles of PON1 increase the risk of carotid artery atherosclerotic disease 22 ; however, the clinical significance of PON1 activity in cardiovascular conditions remains controversial. Some studies have associated low baseline PON1 activity with increased severity of coronary artery disease, while other studies report an association between high baseline PON1 activity and coronary artery disease severity.…”
mentioning
confidence: 99%
“…21 PON1 was also significantly differentially expressed between HF and non-HF patients and significantly associated with HFrEF. Studies in two Japanese patient cohorts have revealed that the presence of certain alleles of PON1 increase the risk of carotid artery atherosclerotic disease 22 ; however, the clinical significance of PON1 activity in cardiovascular conditions remains controversial. Some studies have associated low baseline PON1 activity with increased severity of coronary artery disease, while other studies report an association between high baseline PON1 activity and coronary artery disease severity.…”
mentioning
confidence: 99%
“…As expected, correlation factor in negative acute phase reactant PON1-ARE activity was found to be negative, depending on TNFα in the studied subjects. It has been reported that inflammatory conditions result in PON1 enzymatic activity exhaustion and down regulation of hepatic PON1 mRNA levels [25,26,41]. …”
Section: Resultsmentioning
confidence: 99%